Factors that Influence Behavior in Maintaining Cleanliness Reproductive Organs When Menstruation at SMP PGRI 58 Tanjung Morawa, Deli Serdang - Safitri, Mey Elisa (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2017)
The habit of keeping cleanliness during menstruation, including the cleanliness of reproduction organ, plays an important role in the status of health behavior in order to avoid the problem of the function of the reproduction organ in a woman. The purpose is to avoid infection in the reproduction organ which eventually will lower the quality of her life. The objective of the research was to analyze the influence of knowledge, attitude, availability of facilities, mother’s role, teacher’s role, and peer’s role on behavior of keeping the cleanliness of reproduction organ during menstruation in the female students of SMP PGRI 58 Tanjung Morawa, Deli Serdang District, in 2013. The type of the research was descriptive analytic with cross sectional approach. The population was all 391 female students of SMP PGRI 58 Tanjung Morawa, and 194 werevused as the samples. The data were analyzed by using Chi Square test and multiple logistic regression tests. The result of the research showed that female students who kept their cleanliness of their reproduction organs during menstruation were 49%. There was the influence of the variable of knowledge in cleanliness of reproduction organ during menstruation (p=0.005), the correlation of mother’s role with menstruation (p=0.010), and peer’s role in sharing experiences about menstruation (p=0.007) on behavior of keeping cleanliness of reproduction organ during menstruation. On the other hand, attitude, availability of facilities, and teacher’s role did not have any correlation and influence on behavior of keeping cleanliness of reproduction organ during menstruation. It is recommended that parents and the management of the school increase the behavior of their female students about cleanliness of reproduction organs by improving health socialization of teenager reproduction about cleanliness during menstruation. The socialization is conducted through health education, peer education program, and extracurricular activities.